2020
DOI: 10.3389/fneur.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Interactive Weightless Technology-Aided Intervention and Assessment Picks Out Motor Skills Improvement in Parkinson's Disease: A Pilot Study

Abstract: Background: In Parkinson's disease, reaching movements are conditioned by motor planning and execution deficiency. Recently, rehabilitation, aided by high technological devices, was employed for Parkinson's disease. Objective: We aimed to (1) investigate the changes in the upper limb motor performances in a sample of a patient with Parkinson's disease after a weightless training, with a passive exoskeleton, in an augmented-feedback environment; (2) highlight differences by motor parameters (performance, speed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In a recent systematic review and meta-analysis robotassisted gait training (RAGT) showed better outcomes than conventional interventions on some motor aspects in PD [23], and greater advantages than treadmill training for individuals with freezing of gait-related disability were observed in another study [24]. Upper limb motor performances in patients with PD were also improved after motor training aided by high technological devices [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis robotassisted gait training (RAGT) showed better outcomes than conventional interventions on some motor aspects in PD [23], and greater advantages than treadmill training for individuals with freezing of gait-related disability were observed in another study [24]. Upper limb motor performances in patients with PD were also improved after motor training aided by high technological devices [25].…”
Section: Introductionmentioning
confidence: 99%